2016
DOI: 10.5812/ijvlms.12166
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Virtual Training of Islamic Culture and Civilization Course on Attitude, Learning and Satisfaction of Students in Tehran University of Medical Sciences

Abstract: Background: Nowadays, E-learning is considered as a hot topic in higher education. This study aimed at investigating the effectiveness of virtual training of Islamic culture and civilization course on attitude, learning, and satisfaction of students in University of Medical Sciences in Tehran. Methods: In this quasi-experimental study with two groups, we studied 107 students who took the Islamic culture and civilization course in the second semester of academic year in 2014 -2015. 50.47% of them were Medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…According to the present findings, use of educational technologies can be effective in medical education. As our literature review indicated, incorporation of these tech-nologies as a complementary approach to in-person and traditional methods (42,50,63) or their integration in other educational methods can increase the efficacy of education (24,44). Figure 1 represents the gradually increasing efficacy of educational technologies in the country's medical education.…”
Section: Discussionmentioning
confidence: 99%
“…According to the present findings, use of educational technologies can be effective in medical education. As our literature review indicated, incorporation of these tech-nologies as a complementary approach to in-person and traditional methods (42,50,63) or their integration in other educational methods can increase the efficacy of education (24,44). Figure 1 represents the gradually increasing efficacy of educational technologies in the country's medical education.…”
Section: Discussionmentioning
confidence: 99%
“…Today, e-learning was subjected to change in higher education while also changing the former concept of learning as a new model of modern education. E-learning development provides new virtual facilities for learning and can compensate for the weaknesses of traditional learning methods (2).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, virtual learning environment were designed to promote education and learning. E-learning is becoming more prevalent every day through advancements in technology that provides different educational tools and facilities and also makes educational materials, notifications, contacts, tasks, participation in discussions, teamwork, and quizzes more accessible (2).…”
Section: Introductionmentioning
confidence: 99%